Feed production, swine and slaughterhouse: where is the highest occupational exposure to Aspergillus spp. in this production line? - Viegas, Carla (2016)
Purpose - This study intended to characterize fungal contamination in two swine farms, in one feed production unit, and also in one swine slaughterhouse. We aimed to identify where the highest occupational exposure to Aspergillus spp. was detected during the production line.